Tectonic Characteristics and its Effect on Shale Gas Preservation Condition in the Jingmen Region - Li, Xiaoming; Wang, Yarong; Lin, Wen; Ma, Lihong; Liu, Dexun; Zhang, Yu (Frontiers in Earth Science, 2022)
Jingmen block is a key area for deep shale gas exploration and development. Based on the importance of tectonic characteristics on shale gas preservation conditions, using drilling core observation, seismic data interpretation, analysis of FMI imaging logging results and other methods, on the basis of the analysis and summary of the regional structure, the tectonic characteristics of the Jingmen block and its influence on shale gas preservation were studied. The results show that: (1) The overall structure of the study area is simple, the Upper Ordovician Wufeng Formation-Lower Silurian Longmaxi Formation shale is mainly subjected to compression deformation in Indosinian and early Yanshanian, and extension and strike-slip property transformation in late Yanshanian period, there are back-thrust structures, echelon structures, parallel structures, inversion structures, rifts, etc; (2) Fractures with different tectonic stages and scales have different effects on the preservation degree of shale gas in the study area, resulting in obvious differences in the nature, scale and influence horizon of faults in different regions; (3) The crack associated with fault structure includes interlayer low-angle detachment fracture, conjugate shear fracture, reticular fracture, high-angle shear fracture, high-angle strike slip shear fracture and high-angle fracture zone. The location and type of fracture development in different stages are different, which have different effects on shale gas preservation and migration; (4) Based on the structure's influence on shale gas preservation, the study area is divided into two favorable areas and two more favorable areas.